Molecular Characteristics of Genes and the Immune Microenvironment of a Rare Chest Malignant Tumor (Pulmonary Clear Cell Sarcoma): A Case Report - Xu, Xiaoling; Wang, Ding; Wu, Wei; Lu, Hongyang (Frontiers in Oncology, 2021)
Pulmonary clear cell sarcoma is a rare malignant tumour that has rarely been reported and is challenging to diagnose, especially when differentiating from malignant melanoma. Currently, EWSR1-ATF1 is the key marker for distinguishing clear cell sarcoma from melanoma, but IHC has diagnostic limitations. We report a patient diagnosed with pulmonary clear cell sarcoma, in which a NGS was used to help with the pathological diagnosis. The exposure to the immune microenvironment in pulmonary clear cell sarcoma suggests that TIGIT-related drugs may be a new and effective treatment for this rare disease. Immune microenvironment-related markers, including PD-L1, CD8, TIM3, LAG3 and CD163, were negatively expressed in pulmonary clear cell sarcoma.